OBSTETRIC OUTCOMES IN FEMALES WITH UTERINE FIBROIDS: A STUDY IN A TERTIARY CARE HOSPITAL - IFTIKHAR , A; MUBEEN , S; LEGHARI , N; RAUF , NUA; PARVEEN , A; NISAR , M (Biological and Clinical Sciences Research Journal, 2023)
Uterine fibroids, a type of leiomyoma originating from the myometrium of the uterus, have been associated with adverse consequences during pregnancy. However, the local evidence regarding these outcomes remains scarce. To address this knowledge gap, we conducted a comprehensive study investigating obstetric outcomes among females presenting with fibroid uterus in a tertiary care hospital. This study aimed to provide scientific evidence about uterine fibroids’ impact on pregnancy outcomes. This descriptive case series study was conducted at Unit-IV, Department of Obstetrics and Gynecology, Lady Aitchison Hospital, Lahore, from August 10, 2016, to February 9, 2017. The study aimed to assess obstetric outcomes in females with fibroid uterus during pregnancy. 200 eligible cases were enrolled after obtaining informed consent and demographic information. Participants were followed until obstetric outcomes, including miscarriage, intrauterine demise (IUD), and delivery, occurred. Collected data were entered into SPSS version 17 for analysis. The mean age of the patients was 29.43±5.85 years. Miscarriage and IUD occurred in 15 cases (7.5%) and 19 cases (9.5%). Cesarean section was performed in 107 cases (53.5%), pre-term birth (PTB) occurred in 105 cases (52.5%), intrauterine growth restriction (IUGR) was observed in 17 cases (8.5%), and postpartum hemorrhage (PPH) occurred in 82 cases (41%). These findings suggest a higher frequency of complications, such as cesarean section, PTB, IUGR, and PPH, in females presenting with fibroid uterus during pregnancy, while miscarriage and IUD were less frequent.